Prepreg, laminate, and molded article
By using reinforcing fibers, thermosetting resins and thermoplastic resins in the prepreg, a laminate with excellent bonding strength and compression strength is formed at high temperatures, which solves the problem of insufficient bonding strength of the fiber-reinforced composite materials in the prior art under high temperature environments, and improves process efficiency and material performance.
Patent Information
- Application Number
- CN202411848887.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-23
- Filing Date
- 2020-05-15
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, the bonding strength of the fiber reinforced composite material is insufficient under a high temperature environment, and the mechanical bonding method and the adhesive bonding method have problems such as long process time and reduced material strength.
A prepreg is used, which contains reinforcing fibers, a thermosetting resin and a thermoplastic resin. The thermoplastic resin is present on the surface of the prepreg and is bonded with the thermosetting resin under heating and pressurization to form a laminated body. The laminate exhibits excellent bonding and compression strength at high temperatures.
The excellent bonding strength and compression strength of fiber-reinforced composite materials in high temperature environments are achieved, which shortens the process time and reduces the manufacturing cost.
Smart Images

Figure CN119684743A_ABST
Abstract
Description
[0001] This application is a divisional application of an invention patent application with an application date of May 15, 2020, application number 202080036510.8 (PCT / JP2020 / 019466), and invention name “Prepreg, laminate and molded article”. Technical Field
[0002] The present invention relates to a prepreg comprising reinforcing fibers, a thermosetting resin and a thermoplastic resin, a laminate comprising reinforcing fibers, a thermoplastic resin and a cured product of a thermosetting resin, and a molded product. Background Art
[0003] For the fiber-reinforced composite material formed by using thermosetting resin or thermoplastic resin as a matrix and combining it with reinforcing fibers such as carbon fiber and glass fiber, it is lightweight and has excellent mechanical properties such as strength and rigidity, heat resistance, and corrosion resistance, so it is used in many fields such as aerospace, automobiles, railway vehicles, ships, civil engineering and sports goods. However, these fiber-reinforced composite materials are not suitable for manufacturing parts and structures with complex shapes with a single molding process. In the above-mentioned uses, it is necessary to prepare parts formed by fiber-reinforced composite materials and then integrate them with the same or different parts. As a method for integrating fiber-reinforced composite materials formed by reinforcing fibers and thermosetting resins with the same or different parts, mechanical joining methods such as bolts, rivets, screws, and joining methods using adhesives can be used. In the mechanical joining method, since it is necessary to pre-process the process of the joining part such as the opening, the manufacturing process time becomes longer and the manufacturing cost increases. In addition, there is a problem of reduced material strength due to the opening. The bonding method using an adhesive requires a bonding step including preparation of the adhesive, application of the adhesive, and a curing step, which results in a long manufacturing process time and a problem that reliability cannot be fully satisfied in terms of bonding strength.
[0004] For fiber-reinforced composite materials using thermoplastic resins in the matrix, in addition to the above-mentioned mechanical joining methods and joining using adhesives, methods of joining parts by welding can be applied, so there is a possibility that the time required for joining parts can be shortened. On the other hand, when mechanical properties at high temperatures and excellent resistance to chemicals are required, such as aircraft structural parts, there is a problem that the heat resistance and chemical resistance are insufficient compared to fiber-reinforced composite materials formed of thermosetting resins and reinforcing fibers.
[0005] Here, Patent Document 1 discloses a method of joining a fiber-reinforced composite material composed of a thermosetting resin and reinforcing fibers with an adhesive.
[0006] Patent Document 2 shows a method for integrating a component formed of a thermoplastic resin and a component formed of a fiber-reinforced composite material containing a thermosetting resin. That is, a thermoplastic resin film is laminated on the surface of a prepreg sheet formed of reinforcing fibers and a thermosetting resin and heated and pressurized to obtain a fiber-reinforced composite material. Thereafter, the obtained fiber-reinforced composite material is placed in a mold, and a thermoplastic resin is injection molded, and the formed thermoplastic resin component and the fiber-reinforced composite material are joined by injection molding.
[0007] Patent Document 3 describes a method for producing a laminate having a thermoplastic resin adhesive layer formed on the surface of a composite material composed of a thermosetting resin and reinforcing fibers, and describes that the laminate exhibits an adhesive effect with other members via the thermoplastic resin.
[0008] Patent Document 4 discloses a prepreg and a fiber-reinforced composite material thereof, wherein particles, fibers, or films containing a thermoplastic resin are arranged on the surface layer of a prepreg composed of reinforcing fibers and a thermosetting resin.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2018-161801
[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 10-138354
[0013] Patent Document 3: Japanese Patent No. 3906319
[0014] Patent Document 4: Japanese Patent Application Laid-Open No. 8-259713 Summary of the invention
[0015] Problems to be solved by the invention
[0016] However, since the method disclosed in Patent Document 1 is a method of bonding fiber-reinforced composite materials formed of reinforcing fibers and thermosetting resins to each other using an adhesive, and the thermosetting resin is a matrix resin, welding cannot be applied as a bonding method between fiber-reinforced composite materials as it is. Since the curing of the adhesive takes time, there is a problem that time is required in the bonding process, and the bonding strength exhibited is insufficient.
[0017] In the method described in Patent Document 2, the bonding strength at the bonding portion between the thermosetting resin and the thermoplastic resin film in the fiber-reinforced composite material is insufficient.
[0018] The fiber-reinforced composite material disclosed in Patent Document 3 can be integrated by welding via a thermoplastic resin and exhibits excellent bonding strength at room temperature, but has insufficient bonding strength at high temperatures.
[0019] Patent Document 4 discloses that the interlaminar fracture toughness value can be improved by using particles, fibers or films containing a thermoplastic resin. However, in this method, the bonding strength at the boundary between the thermosetting resin and the thermoplastic resin in the fiber-reinforced composite material is insufficient.
[0020] Therefore, the object of the present invention is to provide a prepreg blank, a laminate and an integrated molded product, which can be joined to the same or different types of parts by welding and show excellent bonding strength, especially excellent bonding strength under high temperature environment. In addition, the compressive strength and interlaminar fracture toughness values are also excellent, and a laminate suitable as a structural material can be provided.
[0021] Means for solving problems
[0022] In order to solve the above-mentioned problems, the prepreg of the present invention has the following structure.
[0023] That is, the prepreg comprises the following components [A], [B] and [C]:
[0024] [A] Reinforcement fibers;
[0025] [B] Thermosetting resin;
[0026] [C] Thermoplastic resin,
[0027] [B] has a rubber modulus of elasticity of 10 MPa or more at a temperature obtained by adding 50°C to the glass transition temperature in a state where the degree of cure is 90% or more, [C] is present on the surface of the prepreg, and in the prepreg, there are reinforcing fibers [A] included in both resin regions astride a boundary surface between a resin region containing [B] and a resin region containing [C].
[0028] Furthermore, the laminated body of the present invention has the following configuration.
[0029] That is, a laminate comprising a layer comprising the following components [A], [C], and [D]:
[0030] [A] Reinforcement fibers;
[0031] [C] Thermoplastic resin;
[0032] [D] Thermosetting resin cured product,
[0033] [D] has a rubber modulus of elasticity of 10 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature, and in the laminate, there are reinforcing fibers [A] included in both resin regions across the boundary surface between the resin region including [C] and the resin region including [D].
[0034] Specifically, the present invention provides the following technical solutions.
[0035] 1. A prepreg comprising the following components [A], [B] and [C]:
[0036] [A] Reinforcement fibers;
[0037] [B] Thermosetting resin;
[0038] [C] Thermoplastic resin,
[0039] [B] has a rubber elastic modulus of 10 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature in a state where the degree of cure is 90% or more,
[0040] [C] exists on the surface of the prepreg,
[0041] In the prepreg, there are reinforcing fibers [A] that are contained in both resin regions, straddling the boundary surface between the resin region containing [B] and the resin region containing [C].
[0042] 2. A prepreg as described in item 1, wherein, in the prepreg viewed from above, when a cross section perpendicular to the plane of the prepreg containing the [A] is obtained from a direction that differs by 45 degrees from the fiber direction of any [A] contained in the two resin regions, in the cross section, the cross-sectional curve formed by the closely fitting boundary surfaces of the two resin regions has a roughness average length RSm defined by JIS B0601 (2001) of less than 100 μm and a roughness average height Rc of more than 3.5 μm.
[0043] 3. The prepreg according to item 1 or 2, wherein the resin region comprising [B] and the resin region comprising [C] are each formed in a layered manner and are adjacent to each other, thereby forming the boundary surface.
[0044] 4. The prepreg according to any one of items 1 to 3, wherein the component [B] has a rubber elastic modulus of 12 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature in a state where the degree of cure is 90% or more.
[0045] 5. The prepreg according to any one of items 1 to 3, wherein the component [B] has a rubber elastic modulus of 15 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature in a state where the degree of cure is 90% or more.
[0046] 6. The prepreg according to any one of items 1 to 5, wherein component [B] comprises an epoxy resin.
[0047] The component [B] contains 40 to 100 parts by mass of a trifunctional or higher-functional glycidylamine-type epoxy resin based on 100 parts by mass of all epoxy resins contained in the component [B].
[0048] 7. The prepreg according to any one of items 1 to 6, wherein the composition comprising component [B] contains an aromatic amine.
[0049] 8. The prepreg according to any one of items 1 to 7, wherein the composition comprising component [B] contains phosphorus at an atomic concentration of 1.0 mass % or less.
[0050] 9. The prepreg according to any one of items 1 to 8, wherein the component [B] has a flexural strength of 150 MPa or more in a state where the degree of cure is 90% or more.
[0051] 10. The prepreg according to any one of items 1 to 9, wherein the roughness average height Rc is 10 μm or more.
[0052] 11. The prepreg according to any one of items 1 to 10, wherein component [C] is one or more selected from a crystalline thermoplastic resin having a glass transition temperature of 80°C or higher or an amorphous thermoplastic resin having a glass transition temperature of 160°C or higher.
[0053] 12. The prepreg according to any one of items 1 to 11, wherein component [C] is one or more selected from polyarylene ether ketone, polyphenylene sulfide or polyetherimide.
[0054] 13. The prepreg according to any one of items 1 to 12, wherein component [A] contains carbon fibers having a strand tensile strength of 5.5 GPa or more.
[0055] 14. A laminate comprising a layer comprising the following components [A], [C] and [D]:
[0056] [A] Reinforcement fibers;
[0057] [C] Thermoplastic resin;
[0058] [D] Thermosetting resin cured product,
[0059] [D] has a rubber elastic modulus of 10 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature.
[0060] In the laminate, there are reinforcing fibers [A] that are included in both resin regions and straddle a boundary surface between a resin region including [C] and a resin region including [D].
[0061] 15. A laminate as described in item 14, wherein, in the laminate viewed from above, when a cross section perpendicular to the plane of the laminate containing the [A] is obtained from a direction that differs by 45 degrees from the fiber direction of any [A] contained in the two resin regions, in the cross section, the cross-sectional curve formed by the closely fitting boundary surfaces of the two resin regions has a roughness average length RSm as defined by JIS B0601 (2001) of less than 100 μm and a roughness average height Rc of more than 3.5 μm.
[0062] 16. The laminate according to item 14 or 15, wherein the resin region containing [C] and the resin region containing [D] are each formed in a layered state and are adjacent to each other, thereby forming the boundary surface.
[0063] 17. The laminate according to any one of items 14 to 16, wherein the component [C] is present on the surface.
[0064] 18. The laminate according to any one of items 14 to 17, wherein the component [C] exists between the layers.
[0065] 19. The laminate according to any one of items 14 to 18, wherein the component [D] has a rubber elastic modulus of 12 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature.
[0066] 20. The laminate according to any one of items 14 to 19, wherein the bending strength of component [D] is 150 MPa or more.
[0067] 21. The laminate according to any one of items 14 to 20, wherein the roughness average height Rc is 10 μm or more.
[0068] 22. The laminate according to any one of items 14 to 21, wherein component [C] is one or more selected from a crystalline thermoplastic resin having a glass transition temperature of 80°C or higher or an amorphous thermoplastic resin having a glass transition temperature of 160°C or higher.
[0069] 23. The laminate according to any one of items 14 to 22, wherein component [C] is one or more selected from polyarylene ether ketone, polyphenylene sulfide or polyetherimide.
[0070] 24. The laminate according to any one of items 14 to 23, wherein component [A] contains carbon fibers having a strand tensile strength of 5.5 GPa or more.
[0071] 25. The laminate according to item 17 or 18, wherein at least a part of the layers is constituted by the cured product of the prepreg according to any one of items 1 to 13.
[0072] 26. A molded article in which another member is joined to the surface of component [C] to thereby integrate the laminated body according to any one of items 17 to 25.
[0073] Effects of the Invention
[0074] The prepreg of the present invention uses a thermosetting resin and a thermoplastic resin, which are firmly joined and can be well welded with the same or different parts, so relative to the fiber-reinforced composite material formed by a thermosetting resin and a reinforcing fiber in the past, the time required in the joining process can be shortened, and the molding of the structural parts can be accelerated. In addition, due to the excellent rubber elastic modulus at a specified temperature, excellent compressive strength and bonding strength under a high temperature environment are exhibited, and a laminate excellent as a structural material can be obtained. For the laminate of the present invention, due to being applicable to computer uses such as aircraft structural parts, blades of windmills, automotive structural parts and IC trays, and shells of notebook computers, etc., excellent performance as a structure is shown, and if the prepreg of the present invention is used, the molding time and molding cost of the products involved in the above-mentioned uses can be greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 The schematic diagram of the prepreg or laminated body according to the present invention is shown in FIG. Figure 2 A view of a cross section of the plane of the prepreg or the plane of the laminate involved.
[0076] Figure 2 It is a schematic diagram of a cross section perpendicular to the plane of the prepreg or the plane of the laminate in the present invention, and is a diagram for explaining the method of measuring the roughness average length RSm and the roughness average height Rc. DETAILED DESCRIPTION
[0077] As the component [A] reinforcing fiber used in the present invention, there are glass fiber, carbon fiber, metal fiber, aromatic polyamide fiber, polyaramid fiber, alumina fiber, silicon carbide fiber, boron fiber, basalt fiber, etc. The above substances can be used alone or in combination of two or more. For the above reinforcing fibers, surface treatment can be applied. As surface treatment, there are metal deposition treatment, treatment using a coupling agent, treatment using a sizing agent, and adhesion treatment of additives. Among the above reinforcing fibers, reinforcing fibers with conductivity are included. As reinforcing fibers, carbon fibers are preferably used because they have a small specific gravity and are high strength and high elastic modulus.
[0078] Commercially available products of carbon fibers include "Torayca (registered trademark)" T800G-24K, "Torayca (registered trademark)" T800S-24K, "Torayca (registered trademark)" T700G-24K, "Torayca (registered trademark)" T700S-24K, "Torayca (registered trademark)" T300-3K, and "Torayca (registered trademark)" T1100G-24K (all manufactured by Toray Co., Ltd.).
[0079] The form and arrangement of the reinforcing fibers can be appropriately selected from: a form and arrangement in which the reinforcing fibers are arranged in one direction; a laminate of objects in which the reinforcing fibers are arranged in one direction; or a woven form, etc. In order to obtain a lightweight laminate with a higher level of durability, in each prepreg, it is preferred that the reinforcing fibers are arranged in one direction in the form of long fibers (fiber bundles) or continuous fibers such as woven fabrics.
[0080] The reinforcing fiber bundle may be composed of multiple fibers of the same form, or may be composed of multiple fibers of different forms. The number of reinforcing fibers constituting one reinforcing fiber bundle is usually 300 to 60,000, and if the manufacture of the substrate is considered, it is preferably 300 to 48,000, and more preferably 1,000 to 24,000. It may also be a range formed by a combination of any of the upper limits and any of the lower limits.
[0081] For the reinforcing fiber of component [A], if the strand tensile strength measured according to the resin impregnation strand test method of JIS R7608 (2007) is 5.5 GPa or more, a laminate having excellent bonding strength in addition to tensile strength can be obtained, which is preferred. If the strand tensile strength is 5.8 GPa, it is further preferred. The bonding strength mentioned here refers to the tensile shear bonding strength determined according to ISO4587:1995 (JIS K6850 (1994)).
[0082] The component [B] used in the present invention is a thermosetting resin having a rubber elastic modulus of 10 MPa or more at a temperature obtained by adding 50°C to the glass transition temperature in a state where the degree of cure is 90% or more. To set the component [B] to a state where the degree of cure is 90% or more, the thermosetting resin of the component [B] and the thermosetting resin composition before curing, which is determined as a curing agent, can be cured by heat treatment under prescribed conditions. Curing by heat treatment under prescribed conditions means first heating at 135°C for 2 hours or 180°C for 2 hours, and then further heating as needed until the degree of cure reaches 90% or more. The degree of cure of the thermosetting resin cured product obtained by heating at 135°C for 2 hours or 180°C for 2 hours is measured. If the degree of cure is 90% or more, the thermosetting resin cured product can be used for property evaluation. When the degree of cure is less than 90% at a heating temperature and time of 135°C for 2 hours or 180°C for 2 hours, post-heating at 180°C for 2 hours is performed to confirm the degree of cure. When the curing degree is less than 90% in the post-heating state, heating is performed at 200°C for 1 hour, 220°C for 1 hour, and 240°C for 1 hour until the curing degree reaches 90%. When the curing degree does not reach 90% even after heating at 240°C for 1 hour, heating is performed at a temperature of 300°C or less until the curing degree reaches 90%, thereby obtaining the target thermosetting resin cured product for property evaluation.
[0083] Here, the degree of cure is the following value, that is, the respective exothermic values of the thermosetting resin composition before curing of the component [B] thermosetting resin and the thermosetting resin composition identified as the curing agent, and the cured product of the thermosetting resin, are calculated by the following formula, respectively, based on the areas of the peaks that appear as exothermic reactions when differential scanning calorimetry is performed at a heating rate of 10°C / min in an inert gas atmosphere. It is also possible to prepare a resin having the same structure as the thermosetting resin and the substance identified as the curing agent separately from the component [B] contained in the prepreg, and provide it for measurement. Here, when the curing agent cannot be determined, 4,4'-diaminodiphenyl sulfone can be used as the curing agent in the above composition. In addition, it is preferred to use a curing catalyst, a viscosity modifier, and other compounds described later in the examples as elements that can constitute the above composition, but these are not particularly limited as long as they do not affect the measurement results.
[0084] Curing degree (%)=((heat release of the composition containing thermosetting resin before curing)-(heat release of the cured product of the thermosetting resin)) / (heat release of the composition containing thermosetting resin before curing)×100.
[0085] In addition, according to JIS K7244-7 (2007), in the dynamic viscoelasticity measurement (torsion measurement) of the thermosetting resin cured product, the storage elastic modulus at a temperature obtained by adding 50°C to the glass transition temperature obtained by using the storage elastic modulus curve is obtained, and is set as the rubber elastic modulus of the present invention. If the rubber elastic modulus of the present invention is less than 10MPa, the compressive strength of the laminate and the bonding strength at high temperature when the laminate is bonded and integrated with the components cannot be fully improved. The rubber elastic modulus is more preferably 12MPa or more, and more preferably 15MPa or more. There is no particular upper limit on the rubber elastic modulus, and the upper limit of the conventional thermosetting resin cured product is 50MPa.
[0086] The thermosetting resin cured product of the component [D] in the present invention can be obtained by heating and curing the thermosetting resin. For the determination of the curing of the component [D] contained in the laminate, if the area of the peak that appears as an exothermic reaction when the laminate is subjected to differential scanning calorimetry at a heating rate of 10°C / min in an inert gas atmosphere (residual exothermic heat) is 50 J / g or less, it can be determined that it is substantially a cured product. Alternatively, when the thermosetting resin composition before curing can be determined, the degree of curing is calculated by the above formula, and if it is 90% or more, it can be regarded as a cured product. When the prepreg of the present invention is used, the thermosetting resin corresponds to the component [B]. The laminate of the present invention does not necessarily have to be obtained via a prepreg, and can also be made by the resin transfer molding method described later.
[0087] The thermosetting resin used in component [B] includes, for example, unsaturated polyester resin, vinyl ester resin, epoxy resin, phenol resin, urea resin, melamine resin, polyimide resin, cyanate resin, bismaleimide resin, benzoxazine resin, or copolymers or modified products thereof, and resins blended with at least two of them. In order to improve impact resistance, an elastomer or rubber component may be added to the thermosetting resin. Among them, epoxy resin is preferred because of its excellent mechanical properties, heat resistance, and adhesion to reinforcing fibers. Examples of the epoxy resin main agent include bisphenol-type epoxy resins such as bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, bisphenol AD-type epoxy resin, and bisphenol S-type epoxy resin, brominated epoxy resins such as tetrabromobisphenol A diglycidyl ether, epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, phenol Novolac-type epoxy resins, cresol Novolac-type epoxy resins, and other Novolac-type epoxy resins, N,N,O-triglycidyl-m-aminophenol, N,N,O-tris-aminophenol, and N,N,O-tris-aminophenol. Glycidylamine type epoxy resins such as hydroglyceryl p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-phenylenediamine, N,N-diglycidyl aniline, N,N-diglycidyl-o-toluidine, resorcinol diglycidyl ether, triglycidyl isocyanurate, etc.
[0088] Component [B] of the present invention: The thermosetting resin preferably includes an epoxy resin. By including a glycidylamine-type epoxy resin containing three or more glycidyl groups in an amount of 40 to 100 parts by mass relative to 100 parts by mass of all epoxy resins contained in the thermosetting resin, a cured product having a high rubber elastic modulus can be obtained, which is a more preferred embodiment. Examples of the glycidylamine-type epoxy resin containing three or more glycidyl groups include N,N,O-triglycidyl-m-aminophenol, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, and N,N,N',N'-tetraglycidyl-m-xylylenediamine.
[0089] Examples of the epoxy resin curing agent include dicyandiamide, aromatic amine compounds, phenol Novolac resins, cresol Novolac resins, polyphenol compounds, imidazole derivatives, tetramethylguanidine, thiourea-added amines, formic hydrazide, formamide, and polythiol.
[0090] Among them, by using an aromatic amine curing agent as a curing agent for an epoxy resin, an epoxy resin with good heat resistance can be obtained. Examples of the aromatic amine compound include 3,3'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-tert-butyl-4,4'-diaminodiphenyl sulfone, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-tert-butyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-tert-butyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-tert-butyl-5,5'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetra-tert-butyl-4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, etc.
[0091] In addition, for the thermosetting resin of component [B], it is preferred that a thermoplastic resin component soluble in the thermosetting resin is contained in a dissolved state as a viscosity modifier. The above-mentioned thermoplastic resin component is a thermoplastic resin component other than component [C]. Here, "soluble in thermosetting resin" means that there is a temperature range in which a uniform phase is formed by heating or heating and stirring the resin obtained by mixing the thermoplastic resin component with the thermosetting resin. Here, "forming a uniform phase" means that a state in which no separation can be visually obtained can be obtained. Here, "dissolved state" means that the thermosetting resin containing the thermoplastic resin component is placed in a certain temperature range and becomes a uniform phase. Once it becomes a uniform phase in a certain temperature range, it does not matter if separation occurs outside the temperature range, for example, at room temperature.
[0092] As a thermoplastic resin component soluble in the thermosetting resin of the constituent element [B], in general, a thermoplastic resin having a bond selected from the group consisting of a carbon-carbon bond, an amide bond, an imide bond, an ester bond, an ether bond, a carbonate bond, a carbamate bond, a thioether bond, a sulfone bond and a carbonyl bond in the main chain is preferred. In addition, for the thermoplastic resin component, it is also possible to partially have a cross-linked structure, and it may be crystalline or amorphous. In particular, it is suitable to be selected from the group consisting of polyamide, polycarbonate, polyoxymethylene, polyphenylene ether, polyphenylene sulfide, polyarylate, polyester, polyamide-imide, polyimide, polyetherimide, polyimide of phenyltrimethylindane structure, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyarylamide, polyvinyl formal, polyvinyl butyral, phenoxy resin, polyether nitrile and polybenzimidazole. In order to obtain good heat resistance, the glass transition temperature is preferably 150° C. or higher, more preferably 170° C. or higher, from the viewpoint of being less likely to cause thermal deformation when used as a molded body. Polyetherimide and polyethersulfone are suitable examples.
[0093] From the perspective of improving flame retardancy, it is also a preferred embodiment to include a phosphorus compound in the composition containing the component [B] thermosetting resin. However, if the amount of phosphorus is large, the bending strength of the thermosetting resin cured product may decrease. Therefore, by setting the phosphorus atom concentration in the above composition to 0.1 mass % or more and 1.0 mass % or less, a thermosetting resin cured product with excellent bending strength can be obtained, which is preferred.
[0094] It should be noted that, regardless of whether or not a phosphorus compound is included, the component [B] contained in the prepreg of the present invention preferably has a bending strength of 150 MPa or more in a state where the degree of cure is 90% or more. In addition, the bending strength of the component [D] contained in the laminate of the present invention is 150 MPa or more. If the above-mentioned cured product is included in the laminate of the present invention, the bonding strength when the laminate is bonded to the component is excellent, so it is preferred. The bending strength can be obtained using a 3-point bending test based on JIS K7171 (1994). When obtaining the bending strength of the above-mentioned components contained in the prepreg or laminate, after determining the type of thermosetting resin, a composition is prepared for the same and uncured resin in the same manner as the above-mentioned determination of the degree of cure for the determination of the bending strength. At this time, it is also possible to prepare a resin of the same structure and uncured separately from the thermosetting resin contained in the prepreg or laminate of the measurement object for measurement. In addition, the upper limit of the flexural strength is not particularly limited, but the upper limit of a cured product of a general thermosetting resin is 500 MPa.
[0095] The thermoplastic resin constituting component [C] is not particularly limited, and examples thereof include polyester resins (polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, liquid crystal polyester, etc.), polyolefin resins (polyethylene, polypropylene, polybutene, etc.), styrene resins, urethane resins, polyoxymethylene, polyamide resins (aliphatic polyamides such as polyamide 6 and polyamide 66, semi-aromatic polyamides, alicyclic polyamides, etc.), polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polyimide, polyamideimide, polyetherimide, polysulfone, modified polysulfone, polyethersulfone, polyketone, polyaryletherketone (polyetherketone, polyetheretherketone, polyetherketoneketone, etc.), polyarylate, polyethernitrile, phenol resin, phenoxy resin, etc. Furthermore, these thermoplastic resins may be copolymers, modified products, and / or resins obtained by mixing two or more kinds of the above-mentioned resins.
[0096] Among them, from the viewpoint of heat resistance, it is preferred that the thermoplastic resin of component [C] contains 60% by weight or more of one or more selected from crystalline thermoplastic resins having a glass transition temperature of 80° C. or more and amorphous thermoplastic resins having a glass transition temperature of 160° C. or more. It is particularly preferred that the thermoplastic resin of component [C] contains 60% by weight or more of one or more selected from polyarylene ether ketone, polyphenylene sulfide and polyether imide.
[0097] In order to improve the impact resistance, an elastomer or a rubber component can be added to the thermosetting resin or the thermoplastic resin. In addition, according to the purpose, the thermosetting resin or the thermoplastic resin may also contain other fillers and additives as appropriate, without prejudice to the purpose of the present invention. For example, inorganic fillers, flame retardants, conductivity imparting agents, nucleating agents, ultraviolet absorbers, antioxidants, vibration damping agents, antibacterial agents, insect repellents, deodorants, anti-coloring agents, heat stabilizers, mold release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, defoamers, coupling agents, etc. can be cited.
[0098] In the prepreg of the present invention, there are reinforcing fibers [A] that are included in both resin regions, straddling the boundary surface between the resin region containing [B] and the resin region containing [C].
[0099] The presence of [A] that straddles the boundary surface between the two resin regions and is contained in the two resin regions can be confirmed by observing a cross section cut perpendicularly to the plane direction. Figure 2 To illustrate an example. Figure 2In the observed image 9, in the case of the prepreg, the resin region 7 containing the component [C] is in close contact with the resin region 8 containing the component [B], and the surface formed by the resin region 7 containing the component [C] and the resin region 8 containing the component [B] is shown as the boundary surface 10. In addition, there are a plurality of components [A] 6 on the boundary surface 10. The component [A] 6 on the boundary surface 10 is in contact with both the resin region 7 containing the component [C] and the resin region 8 containing the component [B]. In the state where the components [C] and [B] are in contact around the reinforcing fibers, it can be said that the reinforcing fibers are in a state of "being included in these two resin regions across the boundary surface".
[0100] Furthermore, when the prepreg of the present invention is viewed from above, in a cross section perpendicular to the plane of the prepreg including the fibers of [A] existing across the above-mentioned two resin regions, obtained from a direction that differs by 45 degrees (whether clockwise or counterclockwise) with respect to the fiber direction of any [A] contained in the above-mentioned two resin regions, that is, in a cross section obtained by cutting perpendicularly to the plane direction of the prepreg, it is preferred that the roughness average length RSm defined by JIS B0601 (2001) of the cross-sectional curve formed by the boundary surfaces of the two resins is 100 μm or less and the roughness average height Rc is 3.5 μm or more.
[0101] In addition, it is preferred that the resin region containing [B] and the resin region containing [C] are each formed in a layered manner and adjacent to each other, thereby forming the aforementioned boundary surface. The term "formed in a layered manner and adjacent to each other" means, for example, Figure 2 The state in which two continuous resin regions exist adjacent to each other as shown can be confirmed by observing a cross section cut perpendicularly to the plane direction of the prepreg.
[0102] The presence of the reinforcing fibers [A] contained in the resin region containing the component [B] and the resin region containing the component [C] across the boundary surface between the two resin regions improves the strength of the resin region containing the component [C] and improves the bonding strength. The component [A] present on the boundary surface chemically and / or physically combines with the components [B] and [C], thereby improving the adhesion with the resin region containing the component [B] and the resin region containing the component [C]. The number of components [A] present on the boundary surface may be one or more, and the upper limit is not particularly limited, but is 200 within the observation range described below.
[0103] The boundary surface between the resin region containing the component [B] and the resin region containing the component [C] can be observed as follows, that is, in the prepreg viewed from above, that is, from a viewpoint perpendicular to the plane direction of the prepreg, from a direction that is 45 degrees (whether clockwise or counterclockwise) different from any fiber direction of [A] contained in the above two resin regions, in a cross section perpendicular to the plane of the prepreg containing the fibers of [A] existing across the above two resin regions. In the cross section, by observing the morphology of the resin region in the boundary surface, the adhesion in the fiber direction and the direction orthogonal thereto can be simultaneously evaluated.
[0104] In the above cross-sectional observation, if the roughness average length RSm of the cross-sectional curve formed by the boundary surface, as defined by JIS B0601 (2001), is less than 100 μm, not only chemical and / or physical bonding forces but also mechanical bonding forces such as so-called interweaving are added, and the resin region containing component [B] and the resin region containing component [C] become difficult to peel off, which is preferred. The lower limit value is not particularly limited, but is preferably 15 μm or more from the viewpoint of avoiding the reduction of mechanical bonding forces caused by stress concentration. In addition, by making the roughness average height Rc of the cross-sectional curve greater than 3.5 μm, not only the mechanical bonding forces caused by interweaving are manifested, but also the component [A] existing on the boundary surface is chemically or / and physically combined with the component [B] and the component [C], and the adhesion between the resin region containing the component [B] and the resin region containing the component [C] is improved, which is preferred. The more preferred range of the roughness average height Rc of the cross-sectional curve is 10 μm or more (component [A] becomes easy to be included in the two resin regions and the adhesion is further improved), and particularly preferably 20 μm or more. The upper limit is not particularly limited, but is preferably 100 μm or less from the viewpoint of avoiding a decrease in mechanical bonding strength caused by stress concentration.
[0105] Here, as a method for measuring the roughness average height Rc and the roughness average length RSm of the cross-sectional curve, a known method can be used. For example, after the component [B] is solidified, a method for measuring by a cross-sectional image obtained using X-ray CT, a method for measuring by an elemental analysis distribution image using an energy dispersive X-ray spectrometer (EDS), or a method for measuring by a cross-sectional observation image using an optical microscope or a scanning electron microscope (SEM) or a transmission electron microscope (TEM). During the observation, in order to adjust the contrast, the component [B] and / or the component [C] may also be stained. In the image obtained by any of the above methods, the roughness average height Rc and the roughness average length RSm of the cross-sectional curve are measured within a range of 500 μm square.
[0106] use Figure 2 An example of a method for measuring the roughness average height Rc and the roughness average length RSm of a cross-sectional curve is shown below (method 1 for measuring cross-sectional curve elements). The end 11 of the rectangular observation image 9 on the side of the resin region containing the component [B] is used as a reference line, and a baseline vertical line 12 is drawn at intervals of 5 μm from the resin region 8 containing the component [B] to the resin region 7 containing the component [C]. The point where the baseline vertical line drawn from the reference line first intersects the component [C] is plotted, and the line connecting the plotted points is set as a cross-sectional curve 13. The obtained cross-sectional curve 13 is screened based on JIS B0601 (2001) to calculate the roughness average height Rc and the roughness average length RSm of the cross-sectional curve 13.
[0107] Furthermore, from the viewpoint of exhibiting excellent mechanical properties, it is preferred that the resin region containing [B] and the resin region containing [C] are each formed in a layered state and are adjacent to each other to form the boundary surface.
[0108] The thermoplastic resin component [C] in the prepreg of the present invention preferably has a weight per unit area of 10 g / m 2 If 10g / m 2 More preferably, it is 20 g / m 2 The upper limit is not particularly limited, but is preferably 500 g / m 2 This is because the amount of thermoplastic resin does not become too much compared to the reinforcing fiber, and a laminate with excellent specific strength and specific elastic modulus can be obtained. 2 The mass (g) of the component [C] contained in the prepreg.
[0109] The prepreg of the present invention preferably has a reinforcing fiber content of 30 to 2,000 g / m 2 If the amount of reinforcing fiber is 30g / m 2 If the amount of reinforcing fiber is 2,000 g / m 2 Below, the drapability of the prepreg becomes easy to improve.
[0110] The reinforcing fiber mass content of the prepreg of the present invention is preferably 30 to 90% by mass, more preferably 35 to 85% by mass, and further preferably 40 to 80% by mass. It can be a range formed by a combination of any of the above upper limits and any of the lower limits. If the reinforcing fiber mass content is 30% by mass or more, the amount of resin will not become too much compared to the fiber, and there is an advantage of being easy to obtain a laminate with excellent specific strength and specific elastic modulus. In addition, when the laminate is formed, the heat release during curing is not easy to become excessively high. In addition, if the reinforcing fiber mass content is 90% by mass or less, poor impregnation of the resin is not likely to occur, and the pores of the resulting laminate are prone to become less.
[0111] The laminate of the present invention satisfies the following aspects: the laminate comprises a layer comprising components [A], [C] and [D], wherein [D] has a rubber modulus of elasticity of 10 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature, and wherein the laminate comprises reinforcing fibers [A] contained in both resin regions across a boundary surface between a resin region comprising [C] and a resin region comprising [D].
[0112] The presence of [A] included in both resin regions across the boundary surface of the two resin regions can be confirmed by observing a cross section cut perpendicularly to the plane direction of the laminate in the same manner as the above-mentioned confirmation method for the prepreg.
[0113] use Figure 2 To illustrate an example. Figure 2In the observed image 9, in the case of the laminate, the resin region 7 containing the component [C] is in close contact with the resin region 8 containing the component [D], and the surface formed by the resin region 7 containing the component [C] and the resin region 8 containing the component [D] is shown as a boundary surface 10. In addition, a plurality of components [A] 6 are present on the boundary surface 10. The component [A] 6 on the boundary surface 10 is in contact with both the resin region 7 containing the component [C] and the resin region 8 containing the component [D]. In the state where the components [C] and [D] are in contact around the reinforcing fibers, it can be said that the reinforcing fibers are in a state of "being included in these two resin regions across the boundary surface".
[0114] In addition, when looking down at the laminate of the present invention, with respect to the fiber direction of any [A] contained in the above-mentioned two resin regions, at an angle of 45 degrees (whether clockwise or counterclockwise) at a viewpoint perpendicular to the plane direction of the laminate, in a cross section perpendicular to the plane of the laminate containing [A] existing across the above-mentioned two resin regions, that is, in an observed cross section obtained by cutting perpendicularly to the plane direction of the laminate, the cross-sectional curve formed by the boundary surface of the two resin regions is preferably formed by the roughness average length RSm defined by JIS B0601 (2001) is 100 μm or less, and the roughness average height Rc is 3.5 μm or more. More preferably, the roughness average height Rc is 10 μm or more. The lower limit of RSm and the upper limit of Rc are not particularly limited. From the viewpoint that the mechanical bonding force may be reduced due to stress concentration, RSm is preferably 15 μm or more, and Rc is preferably 100 μm or less.
[0115] The roughness average height Rc and the roughness average length RSm of the cross-sectional curve can be determined by the above-mentioned method in the same manner as the measurement method of the prepreg of the present invention.
[0116] In addition, from the viewpoint of exhibiting excellent mechanical properties, it is preferred that the resin region containing [C] and the resin region containing [D] are each formed in a layered manner and adjacent to each other to form the aforementioned boundary surface. Figure 2 The state in which two continuous resin regions exist adjacent to each other as shown can be confirmed by observing a cross section cut perpendicularly to the plane direction of the laminate.
[0117] As a method for molding the laminate of the present invention, for example, it can be prepared by using molding methods such as press molding, autoclave molding, bag mold molding, tape winding, internal pressure molding, hand lay-up molding, filament winding, pultrusion, resin injection molding, and resin transfer molding.
[0118] The laminate of the present invention can be produced by the following method, that is, by laminating the above-mentioned prepreg of the present invention alone or together with other prepregs to form at least a part of the layer, and then pressurizing and heating it to cure it. Here, as a method for applying heat and pressure, for example, a press molding method, an autoclave molding method, a bag molding method, a tape wrapping method, an internal pressure molding method, etc. can be used.
[0119] In the laminate of the present invention, the thermoplastic resin of component [C] is present on the surface or between the layers. Preferably, component [C] is present both on the surface and between the layers. By having component [C] of thermoplastic resin present on the surface of the laminate, the laminate of the present invention can be joined to the same or different parts by welding through component [C]. On the other hand, if component [C] of thermoplastic resin is present between the layers of the laminate, an excellent interlaminar fracture toughness value (G IC and G IIC ).
[0120] For the laminate of the present invention, some heating means can be utilized to make other parts, i.e. parts of the same kind and / or different kinds as the parts constituting the laminate (adherends) be joined with the surface constituent element [C] present in the laminate, so as to be integrated (welded) with the laminate through the constituent element [C]. As different kinds of parts (adherends), parts formed by thermoplastic resins and parts formed by metal materials can be cited. For parts formed by thermoplastic resins, reinforcing fibers, fillers, etc. can also be included. The integration method is not particularly limited, and for example, heat welding, vibration welding, ultrasonic welding, laser welding, resistance welding, induction welding, insert injection molding, injection molding on substrate, etc. can be cited.
[0121] The strength of the joint of the integrated parts can be evaluated based on ISO4587:1995 (JIS K6850 (1994)). For the tensile shear bonding strength measured based on ISO4587:1995, it is preferably 25 MPa or more, and more preferably 28 MPa or more when the test environment temperature is 23°C. Generally speaking, if it is 20 MPa or more, the laminate can be used for bonding of structural materials, and it is also high strength compared with the tensile shear bonding strength (about 10 MPa) of general adhesives when the test environment temperature is 23°C. In applications requiring mechanical properties under high temperature environments, when the test environment temperature is 80°C, the evaluation based on ISO4587:1995 shows that a bonding strength of 13 MPa or more is preferred, and more preferably 16 MPa or more. The higher the tensile shear bonding strength, the more preferred it is. There is no particular upper limit. In a conventional integrated molded product of a laminate, 200 MPa is the upper limit for the tensile shear bonding strength at a test environment temperature of 23°C or 80°C.
[0122] The laminate of the present invention is preferably used for aircraft structural parts, wind turbine blades, automobile outer panels and IC trays, computer applications such as notebook computer housings, and sports applications such as golf clubs and tennis rackets.
[0123] Example
[0124] Hereinafter, the present invention will be described in detail using examples. However, the scope of the present invention is not limited to these examples. It should be noted that the unit "part" of the composition ratio refers to mass parts unless otherwise noted. In addition, for the measurement of various properties, it is carried out under an environment of temperature 23° C. and relative humidity 50% unless otherwise noted.
[0125] <Materials used in Examples and Comparative Examples>
[0126] The following components [A], [B], [C], and [D] were used. The components used in each of the Examples and Comparative Examples are shown in Tables 1 to 3.
[0127] Component [A]: Reinforcement fiber
[0128] ·T800: Carbon fiber ("Torayca (registered trademark)" T800S-24K, manufactured by Toray Co., Ltd., strand tensile strength: 5.9 GPa)
[0129] ·T1100: Carbon fiber ("Torayca (registered trademark)" T1100G-24K, manufactured by Toray Co., Ltd., strand tensile strength: 7.0 GPa)
[0130] T700: carbon fiber ("Torayca (registered trademark)" T700S-24K, manufactured by Toray Co., Ltd., strand tensile strength: 4.9 GPa).
[0131] Component [C]: Thermoplastic resin
[0132] PA6: Made of polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Co., Ltd., melting point 225°C, glass transition temperature 48°C)), with a unit weight of 120 g / m 2 membrane
[0133] PPS: Made of polyphenylene sulfide ("Torelina" (registered trademark) A670T05 (manufactured by Toray Co., Ltd., melting point 278°C, glass transition temperature 90°C)), with a unit weight of 120 g / m 2 membrane
[0134] PEKK1: Polyetherketoneketone ("KEPSTAN" (registered trademark) 6002 (produced by Arkema, melting point 300°C, glass transition temperature 160°C)) with a unit weight of 120 g / m 2 membrane
[0135] PEKK2: Polyetherketoneketone ("KEPSTAN" (registered trademark) 7002 (produced by Arkema, melting point 331°C, glass transition temperature 162°C)) with a unit weight of 120 g / m 2 membrane
[0136] PEEK: Made of polyetheretherketone (PEEK 450G (produced by Victrex, melting point 343°C, glass transition temperature 143°C)), with a unit weight of 120 g / m 2 membrane
[0137] PEI: Made of polyetherimide ("ULTEM" (registered trademark) 1010 manufactured by SABIC, glass transition temperature 217°C), with a unit weight of 120 g / m 2 membrane
[0138] Semi-aromatic PA: Made of polyamide 6T (melting point 320°C, glass transition temperature 125°C) with a unit weight of 120 g / m 2 membrane.
[0139] <Evaluation method for thermoplastic resin>
[0140] (1) Method for determining the melting point and glass transition temperature of thermoplastic resins
[0141] The melting point and glass transition temperature of the thermoplastic resin are measured using a differential scanning calorimeter (DSC) based on JIS K7121 (2012). When a plurality of melting points or glass transition temperatures are observed for a mixture, the highest melting point is adopted as the melting point of the thermoplastic resin.
[0142] <Method for preparing and evaluating thermosetting resin composition>
[0143] The thermosetting resin composition of each specific example described in Table 1 was prepared using the following compounds.
[0144] (1) Component [B]: Thermosetting resin (epoxy resin)
[0145] Tetraglycidyl diaminodiphenylmethane ("Araldite" (registered trademark) MY721, manufactured by Huntsman Advanced Materials Co., Ltd.) Epoxy equivalent: 113 (g / eq.), tetrafunctional glycidylamine type epoxy resin)
[0146] Bisphenol A type epoxy resin ("jER" (registered trademark) 825, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 175 (g / eq.)
[0147] · Phenol Novolac type epoxy resin ("jER" (registered trademark) 154, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 178 (g / eq.)
[0148] Bisphenol A type epoxy resin ("jER" (registered trademark) 1001, manufactured by Mitsubishi Chemical Corporation) epoxy equivalent: 475 (g / eq.)).
[0149] (2) Amine compounds
[0150] ·4,4'-Diaminodiphenyl sulfone (Seikacure S, manufactured by Wakayama Seika Industries, Ltd.)
[0151] Dicyandiamide (DICY7, manufactured by Mitsubishi Chemical Corporation).
[0152] (3) Curing catalyst
[0153] 3-(3,4-Dichlorophenyl) 1,1-dimethylurea (DCMU99, manufactured by Hodogaya Chemical Industry Co., Ltd.).
[0154] (4) Viscosity regulator
[0155] Polyethersulfone ("SUMIKA EXCEL" (registered trademark) PES5003P, manufactured by Sumitomo Chemical Co., Ltd.).
[0156] (5) Phosphorus compounds
[0157] Red phosphorus flame retardant ("NOVA red" (registered trademark) 120, manufactured by RIN KAGAKU KOGYO Co., Ltd., phosphorus atom content: 85 mass %).
[0158] (6) Preparation method of thermosetting resin composition
[0159] In a kneading device, the epoxy resin and viscosity modifier listed in Table 1 were added and heated and kneaded to dissolve the viscosity modifier (however, there are cases where the viscosity modifier was not added). Then, the temperature was lowered to 100° C. or lower while the kneading was continued, and an amine compound, a curing catalyst, and a phosphorus compound appropriately selected from the amine compound, a curing catalyst, and a phosphorus compound listed in Table 1 were added (there are cases where the curing catalyst and the phosphorus compound were not added) and stirred to obtain thermosetting resin compositions B-1 to B-10.
[0160] <Method for preparing and evaluating thermosetting resin cured products>
[0161] The thermosetting resin composition prepared by the above method was injected into a mold, and the temperature was raised from 30°C in a heat-sealing dryer at a rate of 1.5°C / min to the curing temperature described in Table 1. After heating and curing for the curing time described in Table 1, the temperature was lowered to 30°C at a rate of 2.5°C / min to prepare a plate-shaped thermosetting resin cured product with a thickness of 2 mm. This is a cured product of the thermosetting resin of component [B] and a cured product of the thermosetting resin of component [D]. Based on the obtained thermosetting resin cured product, each specific example described in Table 1 was evaluated by the following method.
[0162] <Measurement method of glass transition temperature and rubber elastic modulus of cured thermosetting resin>
[0163] A test piece with a width of 12.7 mm and a length of 45 mm was cut out from the resin cured product plate prepared by the above method, and the test piece was dried in a vacuum oven at 60°C for 24 hours, and a storage elastic modulus curve was obtained by a dynamic viscoelasticity test according to JIS K7244-7 (2007). In the storage elastic modulus curve, the temperature value at the intersection of the tangent line in the glass state and the tangent line in the transition state was set as the glass transition temperature. Here, the measurement was performed at a heating rate of 5°C / min and a frequency of 1Hz. The storage elastic modulus at a temperature 50°C higher than the obtained glass transition temperature was set as the rubber elastic modulus.
[0164] <Method for measuring flexural strength of cured thermosetting resin>
[0165] A test piece having a length of 60 mm and a width of 10 mm was cut out from the cured resin plate prepared by the above method, and the test piece was dried in a vacuum oven at 60°C for 24 hours. A three-point bending test was performed using a universal testing machine (manufactured by Instron Japan Company Limited, "Instron" (registered trademark) 5565 Model P8564) at a test speed of 2.5 mm / min and a distance between support points of 32 mm, and the bending strength was determined in accordance with JIS K7171 (1994).
[0166] <Method for preparing prepreg>
[0167] Prepregs were prepared by the following two methods. The components used in each example are shown in Tables 2 and 3, respectively.
[0168] Prepreg [I]
[0169] The component [A] reinforcing fiber (weight per unit area 193g / m 2 ) is pulled out into a reinforcing fiber sheet arranged in a continuous state in one direction, and the reinforcing fiber sheet is made to advance in one direction, and the unit area weight of the component [C] is 120 g / m 2 The resin sheet of the continuous reinforcing fiber sheet is arranged on the continuous reinforcing fiber sheet, and the component [C] is melted by heating with an IR heater and attached to the entire surface of one side of the continuous reinforcing fiber sheet, and the material impregnated in the reinforcing fiber sheet is cooled to obtain a fiber reinforced resin intermediate. The thermosetting resin composition related to the component [B] selected as described in Tables 2 and 3 is coated with a knife coater at a resin unit weight of 100 g / m 2 The thermosetting resin film is coated on release paper, and then the thermosetting resin film is overlapped on the surface of the intermediate opposite to the surface impregnated with the component [C], and the thermosetting resin composition is impregnated into the intermediate while heating and pressing with a hot roller to obtain a prepreg [I].
[0170] Prepreg[II]
[0171] The thermosetting resin composition according to the component [B] selected as shown in Tables 2 and 3 was coated with a knife coater at a resin unit area weight of 50 g / m 2 The resin film was coated on release paper to prepare a resin film. The resin film was overlapped on the reinforcing fibers (weight per unit area 193 g / m) of the component [A] aligned in one direction. 2 ) on both sides, using hot rollers to impregnate the carbon fibers with a thermosetting resin composition while applying heat and pressure, thereby obtaining a prepreg [II].
[0172] <Preparation method of laminate and evaluation of mechanical properties>
[0173] (1) Determination method of tensile shear bond strength
[0174] The prepregs [I] and [II] prepared above were cut into predetermined sizes to obtain two prepregs [I] and six prepregs [II]. The axial direction of the reinforcing fibers was defined as 0°, and the axial orthogonal direction was defined as 90°, and the [0° / 90°] 2s(symbol s represents mirror symmetry) are stacked to prepare a preform. At this time, the two outermost layers of each side of the preform are stacked in a manner that becomes a prepreg [I]. That is, 2 prepregs [I] are stacked with 6 prepregs [II] sandwiched between them. The two surface layers of the preform are configured to become thermoplastic resin layers containing constituent element [C]. That is, it is configured so that the surface of the prepreg [I] impregnated with constituent element [C] becomes the outside. The preform is set in a press molding die, and a clamp and a spacer are used as needed. A pressure of 0.6MPa is applied with a press while maintaining the shape, and heated under the conditions described in Tables 2 and 3, thereby obtaining a laminate. The presence position of constituent element [C] is the surface of the laminate.
[0175] The obtained laminate was cut into two pieces with a width of 250 mm and a length of 92.5 mm, with the 0° direction being the length direction of the test piece, and dried in a vacuum oven for 24 hours. Afterwards, the two panels cut into a shape with a width of 250 mm and a length of 92.5 mm were overlapped in a manner of 25 mm in width × 12.5 mm in length, with the 0° direction being the length direction, and a pressure of 3 MPa was applied at a temperature 20°C higher than the melting point of the thermoplastic resin used as the component [C] and maintained for 1 minute, thereby welding the overlapped surfaces to obtain an integrated molded product. According to ISO4587:1995 (JIS K6850 (1994)), a tab was bonded to the obtained integrated molded product, and cut into a width of 25 mm to obtain the target test piece.
[0176] The obtained test piece was dried in a vacuum oven for 24 hours, and the tensile shear bonding strength was measured at an ambient temperature of 23° C. and 80° C. in accordance with ISO 4587:1995 (JIS K6850 (1994)), and the following evaluation was performed based on the measurement results. The results are shown in the table.
[0177] (a) Tensile shear strength at 23°C
[0178] 28MPa or above: A
[0179] 25MPa or more and less than 28MPa: B
[0180] 20MPa or more and less than 25MPa: C
[0181] Less than 20MPa: D (unqualified)
[0182] (b) Tensile shear strength at 80°C
[0183] 16MPa or above: A
[0184] 13MPa or more and less than 16MPa: B
[0185] 10MPa or more and less than 13MPa: C
[0186] Less than 10MPa: D (unqualified).
[0187] (2) Determination method of compressive strength
[0188] The above-prepared prepregs [I] and [II] are cut into a specified size to obtain 2 prepregs [I] and 4 prepregs [II]. A total of 6 prepregs are stacked in a manner that the 2 outermost layers of each side are set as prepregs [I], and 4 prepregs [II] are sandwiched therebetween and all have the same reinforcing fiber direction to prepare a preform. At this time, the two surface layers of the preform are arranged in a manner that they become thermoplastic resin layers containing constituent element [C]. The preform is set in a press molding die, and a clamp and a spacer are used as needed. A pressure of 0.6MPa is applied by a press machine while maintaining the shape, and heated under the conditions described in Tables 2 and 3 to obtain a laminate. The presence position of constituent element [C] is the surface of the laminate.
[0189] According to SACMA-SRM 1R-94, the wing sheet is bonded to the obtained laminate, and then a rectangular test piece of 80 mm in length and 15 mm in width is cut out with the reinforcing fiber axis direction as the length direction of the test piece. The obtained test piece is dried in a vacuum oven at 60 ° C for 24 hours, and the compressive strength is measured under 23 ° C environment using a material universal testing machine (Instron Japan Company Limited, "Instron" (registered trademark) 5565 type P8564) according to SACMA-SRM 1R-94, and the evaluation is performed as follows based on the measurement results. The results are shown in the table.
[0190] 1.6GPa and above: A
[0191] 1.4GPa or more and less than 1.6GPa: B
[0192] 1.2GPa or more and less than 1.4GPa: C
[0193] Less than 1.2 GPa: D (failed).
[0194] (3) Interlaminar fracture toughness value (G IC and G IIC )
[0195] The prepreg [I] prepared as above is cut into a specified size, and all 20 prepregs are stacked with the surface having the component [C] facing upward so as to have the same reinforcing fiber direction. At this time, a release film for introducing precracks is sandwiched between the 10th and 11th sheets in the center to prepare a preform. The preform is set in a press molding die, and a clamp and a spacer are used as needed. A pressure of 0.6 MPa is applied by a press machine while maintaining the shape, and heated at 180°C for 120 minutes to obtain a laminate. The component [C] exists between the layers of the laminate and on the surface of one side.
[0196] A rectangular test piece with a length of 150 mm and a width of 20 mm was cut from the obtained laminate with the reinforcing fiber axis as the longitudinal direction of the test piece, and dried in a vacuum oven at 60°C for 24 hours. The obtained test piece was evaluated for interlaminar fracture toughness value (G IC and G IIC ).
[0197] <Measurement of the mean roughness length RSm and the mean roughness height Rc in the prepreg or laminate>
[0198] The prepreg [I] or laminate prepared as described above is used. Figure 1 As shown, in the case of a prepreg, with respect to any fiber direction 4 of [A] contained in the two resin regions, an observation section 5 cut perpendicularly to the plane direction of the prepreg at an angle of 45 degrees from a top view of the prepreg, i.e., a viewpoint perpendicular to the plane direction of the prepreg, is photographed using an optical microscope at 1000 times. Within an arbitrary 500 μm square observation range in the obtained image, the roughness average length RSm and the roughness average height Rc defined by JIS B0601 (2001) of the cross-sectional curve element obtained by the above-mentioned cross-sectional curve element measurement method 1 are measured. The same is true for the case of a laminate.
[0199] <Examples 1 to 16>
[0200] In Examples 1 to 16, laminates were produced by the method described in (1) the method for measuring tensile shear bond strength and the method described in (2) the method for measuring compressive strength.
[0201] <Examples 1 to 3>
[0202] As shown in Table 1, in Examples 1 to 3, as the amount of trifunctional or higher glycidylamine epoxy resin (tetraglycidyldiaminodiphenylmethane) added increases, the rubber elastic modulus of the cured thermosetting resin tends to increase. As shown in Table 2, as the amount of tetraglycidyldiaminodiphenylmethane added increases, the tensile shear bond strength and the compressive strength increase, showing a preferred tendency.
[0203] <Example 1 and Comparative Examples 1 and 2>
[0204] In Example 1, as shown in Table 2, by using a thermosetting resin with a high rubber elastic modulus as component [B], the laminate exhibits excellent tensile shear bonding strength and compressive strength compared to Comparative Examples 1 and 2 shown in Table 3 (the rubber elastic modulus of the thermosetting resin is less than 10 MPa).
[0205] <Example 1 and Examples 4 and 5>
[0206] As shown in Table 1, in Example 4 and Example 5, a thermosetting resin composition different from that in Example 1 was used. As shown in Table 2, the tensile shear bonding strength and compressive strength at 80°C showed a tendency to decrease slightly compared with Example 1, but both showed excellent properties.
[0207] <Example 1 and Examples 6 and 7>
[0208] As shown in Table 1, in Examples 6 and 7, as compared with Example 1, as the amount of phosphorus compound added increased, the bending strength of the thermosetting resin cured product tended to decrease. As shown in Table 2, the tensile shear bonding strength at 23°C and the tensile shear bonding strength at 80°C tended to decrease slightly, but both showed excellent properties.
[0209] <Example 1 and Example 8>
[0210] As shown in Table 2, Example 8 was prepared in the same manner as Example 1 except that the viscosity modifier was not used. As shown in Table 2, Example 8 exhibited excellent properties similar to those of Example 1.
[0211] <Examples 1 and 9, 10>
[0212] As shown in Table 2, in Examples 9 and 10, reinforcing fibers having different strand tensile strengths were used. As compared with Example 1, the higher the strand tensile strength, the higher the tensile shear bonding strength at 23°C and the tensile shear bonding strength at 80°C, showing preferred characteristics.
[0213] <Example 1 and Examples 11 to 16>
[0214] As shown in Table 2, in Examples 11 to 16, component [C] having a higher glass transition temperature than that of Example 1 was used. As a result, the tensile shear bonding strength at 80° C. was improved compared to that of Example 1, showing preferable characteristics.
[0215] <Example 1 and Comparative Example 3>
[0216] The two sides of the reinforcing fiber sheet arranged in a plane in one direction are attached with a film having a unit area weight of 50g / m 2 A film of polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Co., Ltd.)) was heated and pressed at 250°C to obtain a reinforced carbon fiber with a unit weight of 193 g / m 2 The obtained prepreg was cut into a predetermined size and cut into [0° / 90°] pieces for evaluation of bonding strength and evaluation of compressive strength. 2s Alternatively, after stacking 6 sheets in the same direction, a pressure of 3 MPa was applied by a press machine, and heated at 250°C for 10 minutes to obtain a laminate. The obtained laminate was measured for bonding strength and compressive strength by the method described in the examples. As shown in Table 3, since no thermosetting resin was contained, the tensile shear bonding strength and compressive strength at 80°C were lower than those in Example 1, and sufficient properties as a structural material were not shown.
[0217] <Example 17 and Comparative Examples 4 and 5>
[0218] In Example 17, (3) interlaminar fracture toughness value (G IC and G IIC ) is prepared by the method described in the determination method of . The above-mentioned prepreg [I] is cut into a specified size, and all the prepregs totaling 20 sheets are stacked with the surface containing the component [C] facing upward in a manner to have the same reinforcing fiber direction, and a release film for introducing precracks is sandwiched between the 10th and 11th sheets in the center to prepare a preform. In Comparative Example 4, the prepreg [II] (not containing the component [C]) is cut into a specified size, and stacked in the same manner as in Example 17, and a release film is sandwiched to obtain a preform. In Comparative Example 5, polyamide particles (SP-500, manufactured by Toray Co., Ltd.) are added so that the particle amount per unit area of the prepreg becomes 7g / m 2After being evenly spread in a manner, the preform was laminated on one side of a prepreg [II] (not including component [C]) cut into a predetermined size in the same manner as in Example 17, and a release film was sandwiched therebetween to obtain a preform. In Example 17 and Comparative Examples 4 and 5, a pressure of 0.6 MPa was applied to the obtained preform by a press machine, and the preform was heated at 180°C for 120 minutes to obtain a laminate, and then the interlaminar fracture toughness value (G IC and G IIC As shown in Tables 2 and 3, Example 17 including the component [C] between the layers of the laminate exhibited an excellent interlaminar fracture toughness value compared to Comparative Example 4 not including the component [C] and Comparative Example 5 including the thermoplastic resin in a different form.
[0219] [Table 1]
[0220]
[0221] [Table 2-1]
[0222]
[0223] [Table 2-2]
[0224]
[0225] [Table 3]
[0226]
[0227] Description of Reference Numerals
[0228] 1: One layer of a prepreg or laminate
[0229] 2: Constituent elements [A]
[0230] 3: Component [C] and component [B] or component [C] and component [D]
[0231] 4: Fiber direction
[0232] 5: Observe the cross section
[0233] 6: Constituent elements [A]
[0234] 7: Resin area including component [C]
[0235] 8: A resin region including component [B] or a resin region including component [D]
[0236] 9: Observe the image
[0237] 10: Boundary surface
[0238] 11: Baseline
[0239] 12: Baseline vertical line
[0240] 13: Section curve
Claims
1. A prepreg comprising the following components [A], [B] and [C]: [A] Reinforcement fibers; [B] Thermosetting resin; [C] Thermoplastic resin, [B] has a rubber elastic modulus of 10 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature in a state where the degree of cure is 90% or more, [C] exists on the surface of the prepreg, In the prepreg, there are reinforcing fibers [A] included in the resin region [B] and the resin region [C] across the boundary between the two resin regions, The resin region containing [B] and the resin region containing [C] are each formed in a layer shape and are adjacent to each other, thereby forming the boundary surface.
2. The prepreg according to claim 1, wherein In the prepreg when viewed from above, when a cross section perpendicular to the plane of the prepreg containing the [A] is obtained from a direction that differs by 45 degrees from the fiber direction of any [A] contained in the two resin regions, in the cross section, the cross-sectional curve formed by the closely fitting boundary surfaces of the two resin regions has a roughness average length RSm defined by JIS B0601 (2001) of less than 100 μm and a roughness average height Rc of more than 3.5 μm.
3. The prepreg according to claim 1 or 2, wherein: Component [B] has a rubber elastic modulus of 12 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature in a state where the degree of cure is 90% or more.
4. The prepreg according to claim 1 or 2, wherein: Component [B] has a rubber elastic modulus of 15 MPa or more at a temperature obtained by adding 50° C. to the glass transition temperature in a state where the degree of cure is 90% or more.
5. The prepreg according to claim 1 or 2, wherein: Component [B] comprises epoxy resin, The component [B] contains 40 to 100 parts by mass of a trifunctional or higher-functional glycidylamine-type epoxy resin based on 100 parts by mass of all epoxy resins contained in the component [B].
6. The prepreg according to claim 1 or 2, wherein: The composition comprising component [B] contains an aromatic amine.
7. The prepreg according to claim 1 or 2, wherein: The composition including component [B] contains phosphorus at an atomic concentration of 1.0 mass % or less.
8. The prepreg according to claim 1 or 2, wherein: The component [B] has a flexural strength of 150 MPa or more in a state where the degree of cure is 90% or more.
9. The prepreg according to claim 2, wherein: The roughness average height Rc is greater than or equal to 10 μm.
10. The prepreg according to claim 1 or 2, wherein: Component [C] is one or more selected from a crystalline thermoplastic resin having a glass transition temperature of 80° C. or higher or an amorphous thermoplastic resin having a glass transition temperature of 160° C. or higher.
11. The prepreg according to claim 1 or 2, wherein: Component [C] is one or more selected from polyarylene ether ketone, polyphenylene sulfide or polyether imide.
12. The prepreg according to claim 1 or 2, wherein: Component [A] contains carbon fibers having a strand tensile strength of 5.5 GPa or more.
Citation Information
Patent Citations
Prepreg and fiber-reinforced composite material
JP1996259713A
Carbon fiber reinforced resin molded product and its manufacture
JP1998138354A
Adhesion structural member
JP2018161801A